THE PREVALENCE OF POST TRAUMATIC GROWTH AMONG TROOPS IN POST DEPLOYMENT PHASE: Post Traumatic Growth in Post Deployment Phase - Mohsin, Shamaila; Rahman, Mahmood ur; Rana, Mowadat Hussain; Azam, Naila; Masood, Sumaira (Pakistan Armed Forces Medical Journal, 2016)
Objective: To determine the prevalence of post-traumatic growth (PTG) and its association with socio demographic factors among a cohort of troops in post deployment phase.Study Design: Descriptive cross sectional.Place and Duration of Study: A Military battalion in Lahore from Jan-April 2015, one year after deployment in the combat area.Material and Methods: A sample of 296 combat troops was selected using non-probability convenient sampling technique. After taking informed written consent the data was collected using Urdu version of psychometric tool Post Traumatic Growth Inventory (PTGI). Data was entered and analyzed SPSS version 20.Results: The mean age of the respondents was 29 ± 6.2 years. Married and unmarried were 214 (72.3%) and 82 (27.7%) respectively. The mean years of service of the troops were 11. In our study the majority of troops 279(94.3% ) exhibited greater degree of positive growth (≥75) ,15 ( 5.1%) had moderate degree of positive growth (74-51) while only 2( 0.7%) had no post traumatic growth(≤50). There was a significant negative correlation of PTG with the age (p < 0.01) and a significant association of Ethnicity with PTG (p=0.03). However there was no significant association of PTG with marital status (p= 0.06), education (p=0.52), income (p=0.71), rank (p= 0.96) and years of service (p= 0.49) at 95% confidence level.Conclusion: It was concluded that there was a high prevalence of resilience as PTG in majority of troops one year after deployment in a combat area.